Small groups as complex systems : formation, coordination, development and adaptation - Arrow, Holly (Sage Publications, 2000)
This general theory of small groups as complex systems draws on general systems theory, dynamical systems theory, and complexity and chaos theory in offering a more complete understanding of the nature of group behaviour and the factors which shape it.